Analisis Pengaruh Stres Institusional terhadap Kinerja Anggota Polres Murung Raya Polda Kalteng Melalui Motivasi Kerja Sebagai Variabel Intervening - Yurianto; Roby Sambung; Shine Pintor Siolemba Patiro (Syntax Literate, 2023)
This research aims to determine the extent of the influence of Institutional Stress on the Performance of members of the Murung Raya Police Resort in Central Kalimantan Regional Police through Work Motivation as an intervening variable. The variables examined in this study are Variable X (Institutional Stress), Variable Z (Work Motivation), and Variable Y (Performance). The sampling method used in this research is a survey research method, where the entire population of 269 members of the Murung Raya Police Resort in Central Kalimantan Regional Police participated in the sampling. Variable X has an influence on Variable Y. The purpose of this research is to determine the extent of the influence of Variable X on Variable Z and to determine the extent of the influence of Variable Z on Variable Y. The results of the first hypothesis test, whether Institutional Stress (X1), has a positive effect on the Performance of Members (Y), show that there is no significant influence. This is evidenced by the P-Values having a value of 0.460, which is greater than the significance level of 0.05 (5%). The results of the second hypothesis test, whether institutional stress (X1), has a positive effect on work motivation (Z), show that there is a significant influence. It has a value of 0.000, which is smaller than the significance level p-value of 0.05 (5%). The results of the third hypothesis test to examine whether work motivation (Z) has a positive effect on the performance of members (Y) show that there is a significant influence. It has a value of 0.000, which is smaller than the significance level p-value of 0.05 (5%).